Effect of IX dosing on polypropylene and PVDF membrane fouling control - Myat, D.; Mergen, M.; Zhao, O.; Stewart, M.; Orbell, J.; Merle, T.; Croué, Jean-Philippe; Gray, S. (IWA Publishing, 2013)
The performance of ion exchange (IX) resin for organics removal from wastewater was assessed using advanced characterisation techniques for varying doses of IX. Organic characterisation using liquid chromatography with a photodiode array (PDA) and fluorescence spectroscopy (Method A), and UV254, organic carbon and organic nitrogen detectors (Method B), was undertaken on wastewater before and after magnetic IX treatment. Results showed partial removal of the biopolymer fraction at high IX doses. With increasing concentration of IX, evidence for nitrogen-containing compounds such as proteins and amino acids disappeared from the LC-OND chromatogram, complementary to the fluorescence response. A greater fluorescence response of tryptophan-like proteins (278nm/343nm) for low IX concentrations was consistent with aggregation of tryptophan-like compounds into larger aggregates, either by self-aggregation or with polysaccharides. Recycling of IX resin through multiple adsorption steps without regeneration maintained the high level of humics removal but there was no continued removal of biopolymer. Subsequent membrane filtration of the IX treated waters resulted in complex fouling trends. Filtration tests with either polypropylene (PP) or polyvinylidene fluoride (PVDF) membranes showed higher rates of initial fouling following treatment with high IX doses (10mL/L) compared to filtration of untreated water, while treatment with lower IX doses resulted in decreased fouling rates relative to the untreated water. However, at longer filtration times the rate of fouling of IX treated waters was lower than untreated water and the relative fouling rates corresponded to the amount of biopolymer material in the feed. It was proposed that the mode of fouling changed from pore constriction during the initial filtration period to filter cake build up at longer filtration times. The organic composition strongly influenced the rate of fouling during the initial filtration period due to competitive adsorption processes, while at longer filtration times the rate of fouling appeared to depend upon the amount of biopolymer material in the feed water.